Transitioning University Courses Online in Response to COVID-19 - David Michael Telles-Langdon (University of Windsor, 2020)
As the world reeled from the realization that a pandemic of a magnitude not seen in a century was upon us, and that physical distancing to reduce the speed of transmission was going to necessitate suspension of regular classes, university faculty members scrambled to convert their planned lectures from in-person to online formats. This article describes one faculty member's experiences using a flipped classroom approach in a virtual teaching environment. The arrival of COVID-19 fractured the school year and put some students' graduation in jeopardy. From a hasty search of literature on the process of teaching and evaluating in an online environment, to a selection of hardware and software to provide students with an optimal learning environment while ensuring the security and validity of online evaluation, this article will highlight some of the successes and pitfalls of a rapid transition to online instruction and evaluation. Although there is a body of literature on the process and efficacy of online teaching, the constantly evolving nature of technology not only continues to produce new online instruction tools, but also tools that can be used by students to circumvent most cheating prevention measures put in place.